2014
DOI: 10.1007/s10653-014-9599-2
|View full text |Cite
|
Sign up to set email alerts
|

Geological factors controlling occurrence and distribution of arsenic in groundwaters from the southern margin of the Duero Basin, Spain

Abstract: Groundwater from springs and boreholes on the southern edge of the Cenozoic Duero Basin (DB) of Spain has concentrations of arsenic (As) which are commonly above the EC drinking-water limit of 10 µg/L, and reach observed values up to 241 µg/L. Groundwater compositions within the sedimentary aquifer vary from Ca-HCO 3 type, variably affected by evaporation and agricultural pollution at shallow levels, to Na-HCO 3 compositions in deeper boreholes of the basin. Groundwater conditions are mainly oxidising but redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
1
5
0
3
Order By: Relevance
“…Towards the north, in the centre of the study area, a crossshaped distribution can be identified following these main fracture orientations. This distribution corroborates earlier theories about the control exercised by the structure of the basement on the distribution of As (Giménez-Forcada and Smedley, 2014;Rey-Moral et al, 2016;Giménez-Forcada et al, 2017).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Towards the north, in the centre of the study area, a crossshaped distribution can be identified following these main fracture orientations. This distribution corroborates earlier theories about the control exercised by the structure of the basement on the distribution of As (Giménez-Forcada and Smedley, 2014;Rey-Moral et al, 2016;Giménez-Forcada et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…Analyses of sediment samples undertaken as part of the various studies cited indicate that the clayey-silty materials contain the highest concentrations of As. Furthermore, and without disregarding water-sediment interactions, recent studies of the distribution of As within the area allude to the distribution of As in the southern CDB being strongly controlled by the structure of the Basin (Giménez-Forcada and Smedley, 2014;Rey-Moral et al, 2016;Giménez-Forcada et al, 2017).…”
Section: +mentioning
confidence: 99%
“…A esta estructura se asocian las cuencas pull-apart terciarias del Valle Amblés y Corneja, que forman parte también de la zona de estudio. Se han detectado anomalías significativas de As en la prolongación de esta estructura bajo el relleno terciario de la cuenca del Duero (Giménez-Forcada y Smedley, 2014;Rey-Moral et al, 2016). Aproximadamente la cuarta parte de la provincia de Ávila corresponde a los depósitos terciarios de la Cuenca del Duero, mientras que el resto del territorio se encuentra sobre el Sistema Central (Figura 2).…”
Section: áRea De Estudio Y Datos De Concentración De Asunclassified
“…Este último método utiliza la geología para el cálculo de la media local variable, dando como resultado un mapa más detallado que los métodos que utilizan sólo las concentraciones de As (Figura 4(c)). Por otro lado todos los mapas que han tenido en cuenta la litología de la zona estudiada (Figuras 4 (c), (e) y (f)) reflejan un mayor contraste entre las áreas sedimentarias (con altas concentraciones de As en las aguas subterráneas) y las del Sistema Central, donde generalmente los valores de concentración de As son más bajos, a excepción de las 2017, IWA Publishing, Editorial UPV, FFIA fracturas donde se aprecia un HGT As mayor, especialmente en torno al trazado del dique Messejana-Plasencia, corroborando de este modo la hipótesis sobre el control estructural de la distribución de As (Giménez-Forcada y Smedley, 2014;Rey-Moral et al, 2016).…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation